English Teachers Perceptions Of The Development Of An Independent Curriculum - Dwi Putri Juwita Zebua (Jurnal Motivasi Pendidikan dan Bahasa, 2024)
This research is entitled "English Teachers' Perceptions of Independent Learning Curriculum Development". This aims to find out and understand teachers' perceptions of the current development of the independent curriculum and also whether there are any obstacles from both teachers and students, as well as what their hopes are for the future curriculum. This study uses a qualitative method. By interviewing several English teachers and there is some data related to the teachers who have been interviewed, I can conclude that the development of the independent curriculum has been quite helpful in several aspects, but teachers cannot give one hundred percent in implementing the independent curriculum at this time because the current curriculum is still just being implemented.